Economic, political and symbolic management of “traditional knowledge”: the construction of a self-identity in a globalized world (2011)
This paper is the introduction to the dossier with three articles resulting from the Symposium “Economic, Political and Symbolic Management of ‘Traditional Knowledge’: Indigenous Criteria and External Redefinitions” of the 53rd International Congress of Americanists (Mexico, 2009). We have modified the subtitle of the Symposium, adopting in exchange for this dossier the subtitle of the Congress’ motto: “The Construction of a Self-Identity in a Globalized World”. The first part of the text remembers Ana María Spadafora, co-organizer of the Symposium and editor of the dossier, who passed away in 2010. The second part presents the aim of the Symposium and the contribution of the three articles in the dossier, plus Ana María Spadafora’s article, which was published earlier in this journal. Even though they touch on quite different research fields—bio-trade in Mexico and Peru, commercialization of handicrafts in French Guiana, modifications of traditional knowledge among the Ashéninka of Peru, and dreams of Pilagá women of the Chaco as practical action—all four papers show that the emphasis on relational aspects, the polyvalence of thoughts and practices or the imbrication of speaking, thinking and doing are stronger constants than the persistence of this or that emblematic element of “ethnic tradition.”